The atypical antipsychotics and sexual dysfunction: a pharmacovigilance-pharmacodynamic study - Cheng, Yu; Chen, Youjun; Zhao, Xue; Mou, Fan; Wang, Wanying; Qian, Ruiyi; Huang, Jingjing; Li, Huafang; Xu, Qingqing; Yu, Shunying (Frontiers in Pharmacology, 2024)
Background: Sexual dysfunction (SD) induced by atypical antipsychotics (AAPs) is a frequent issue in clinical practice but under-estimated by clinicians, and is not extensively researched. The current study aimed to quantify the strength of association between the use of different AAPs and SD using real-world data from the FDA Adverse Event Reporting System (FAERS), as well as investigate the receptor mechanisms that are involved.Methods: Data from the FAERS database from the first quarter of 2004 to the third quarter of 2023 were queried through OpenVigil 2.1. Disproportionality analysis was estimated using the reporting odds ratio (ROR) and information components (IC) methods, and linear regression was used to investigate the relationship between ROR and receptor occupancy which was estimated using in vitro receptor binding profiles.Results: Our analysis yielded 4839 reports that co-mentioned AAP and SD events, and the findings revealed statistical associations between 12 AAPs and SD. The highest signal value was identified for iloperidone reporting retrograde ejaculation with iloperidone (ROR = 832.09; IC = 9.58), followed by compulsive sexual behavior with aripiprazole (ROR = 533.02; IC = 7.30), and psychosexual disorder for aripiprazole (ROR = 145.80; IC025 = 6.47).Different characteristics of the SD side effects in each AAPs were discovered after further data mining. Regression analysis revealed potential effects for receptor occupation of D2, D3and 5-HT1A receptors on ROR. However, no significant correlation persisted following sensitivity analyses.This is the first study to investigate the AAP-SD associations by using FAERS.In this study, we report for the first time a significant association between aripiprazole and SD based on real-world data. The study suggests that different AAPs have varying levels of association with SD, and the D2, D3 and 5-HT1A receptor occupation may contribute to potential mechanisms. The findings of this study warrant further validation of more studies and clinical causality assessment.